Peningkatan Pemahaman Konsep Keanekaragaman Hayati melalui Model Pembelajaran Biologi Berbasis Lingkungan - Nursidin Nursidin; Rusman Rusman; Laksmi Dewi (BIOEDUSCIENCE, 2022)
Background: Indonesia has abundant biodiversity. The concept of biodiversity was chosen because there are still places that must be known that students can use as learning resources. The learning innovation carried out is the application of environment-based knowledge to improve students' understanding of the concept of biodiversity. Method: This study used a pretest-posttest group design, 105 students of class X SMA Negeri Asera. The research sample consisted of 2 classes, namely the experimental and control classes. The experimental class uses environment-based learning and the control class uses conventional learning. The data was obtained through a test of understanding the concept of biodiversity and interviews. Data analysis was carried out by descriptive analysis and inferential statistics. Hypothesis testing through t-test using SPSS 20.0 program. Result: There is a difference in values between the experimental and control classes, where the experimental class values are higher than the control class values with that = 10,899. Conclusion: The application of this environment-based learning can affect student learning outcomes of SMA Negeri Asera.